Communication, cooperation and collusion in team tournaments: An experimental study - Matthias Sutter; Christina Strassmair (University of Innsbruck, Department of Public Finance, 2007)
We study the effects of communication in an experimental tournament between teams. When teams, rather than individuals, compete for a prize there is a need for intra-team coordination in order to win the inter-team competition. Introducing communication in such situations may have ambiguous effects on effort choices. Communication within teams may promote higher efforts by mitigating the internal free-rider problem. Communication between competing teams may lead to collusion, thereby reducing efforts. In our experiment we control the channels of communication by letting subjects communicate through an electronic chat. We find, indeed, that communication within teams increases efforts and communication between teams reduces efforts. We use team members? dialogues to explain these effects of communication, and check the robustness of our results.
Keywords: C92; J33; 330; tournament; team decision making; communication; collusion; freeriding; experiment; Wettbewerb; Kommunikation; Arbeitsgruppe; Test; Theorie